2017
DOI: 10.1016/j.ijrobp.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Patient Reporting of Symptomatic Adverse Events via the Patient-Reported Outcomes Version of the Common Terminology Criteria for Adverse Events (PRO-CTCAE) in a Chemoradiotherapy Cooperative Group Multicenter Clinical Trial

Abstract: Purpose To assess the feasibility of measuring symptomatic adverse events (AEs) in a multicenter clinical trial using the National Cancer Institute’s Patient-Reported Outcomes version of the Common Terminology Criteria for Adverse Events (PRO-CTCAE). Methods and Materials Patients enrolled in Trial XXXX (XXXX) were asked to self-report 53 PRO-CTCAE items representing 30 symptomatic AEs at 6 time points (baseline; weekly x4 during treatment; 12-weeks post-treatment). Reporting was conducted via wireless table… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 11 publications
5
64
0
1
Order By: Relevance
“…Recently, Basch et al 304 showed that self-evaluation of symptoms could significantly improve QoL during treatment, decrease emergency admissions, and even improve survival of patients with advanced cancers. The possible negative impact of treatment on QoL due to AEs should be considered and balanced against the possible positive effects of treatment to reduce or delay cancer symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Basch et al 304 showed that self-evaluation of symptoms could significantly improve QoL during treatment, decrease emergency admissions, and even improve survival of patients with advanced cancers. The possible negative impact of treatment on QoL due to AEs should be considered and balanced against the possible positive effects of treatment to reduce or delay cancer symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Standardized reporting is now available through the National Cancer Institute's Patient-Reported Outcomes-CTCAE (PRO-CTCAE) scales [10][11][12][13]. Efforts are underway to integrate PRO-CTCAE measurement into clinical trials [14][15][16][17][18][19], and interest is growing in the implementation and utilization of patient-reported symptom monitoring in patient-centered clinical practice [20][21][22][23][24][25][26][27][28][29]. Like CTCAE, the focus of PRO-CTCAE is continuous symptom monitoring throughout chemotherapy, not just at the beginning and end of chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Patient representatives were active participants throughout the development of this measure and a wider group of patients was involved in providing detailed feedback at several points in the process . Basch and colleagues have shown that patients are willing and able to complete the PRO‐CTCAE for the collection of adverse event recording and that minimal additional resources are required . Making the use of a PRO on AEs mandatory may provide a better assessment of the balance between the efficacy and toxicity of cancer treatments …”
Section: The Patient and Patient Advocate Contributionmentioning
confidence: 99%